Pengembangan media komik IPA berbasis sets plus national building untuk peserta didik sekolah menengah pertama (SMP) - Ani Widyawati; Laily Rochmawati Listiyani (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2018)
The objective of this research were (1) to know the characteristic of sciece comic based on SETS plus national building; (2) to know the feasibility of science comic and; (3) to know the effectiveness of science comic. This research used Research and Development method with seven stages, these are: introduction, planning, developing, early try out, revision, limited try out and final product revision. The subject of this research was student of SMP Muhammadiyah 2 Yogyakarta grade VII consist of 30 students. The data collecting instruments are validation sheet for media and science material expert, observation sheet, and students’ character questionnaire. The result of this research are 1) the characteristic of science comic were include national building and associated with SETS approach; 2) the feasibility of science comic is considered very good to use; and 3) the science comic applicate to develop student’s nasionalism character